2018
DOI: 10.4236/nr.2018.92003
|View full text |Cite
|
Sign up to set email alerts
|

Mineralogical and Petrographic Characteristics of Indium and REE-Bearing Accessory Phases in the Kymi Granite Stock, Southern Finland

Abstract: The Wiborg rapakivi batholith (1.64 Ga) in southeastern Finland with documented occurrences of REE, indium and Zn-Cu-Pb sulphide mineralization was studied. Hydrothermal greisen and quartz vein type Fe-Sn and Zn-Cu-Pb are found in the Kymi granite stock as intrusions. They are enriched with indium and rare earth elements, with roquesite (CuInS 2 ) being a major indiumcarrier, whereas monazite (Ce), allanite (Ce), bastnäesite (Ce), xenotime-(Y) and thorite are the main REE carriers. Combination of optical and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…As it is expected, and also demonstrated by many other studies [63,64], LREE are generally enriched in monazite, allanite and carbonate minerals, whereas xenotime concentrates HREE regardless the conditions of crystallization. The highest average LREE concentrations at around 60 wt % occur in monazite, bastnäsite and synchysite, but the range of these values is highly variable.…”
Section: Compositions Of Ree Minerals With Different Origins In Finlandmentioning
confidence: 49%
See 2 more Smart Citations
“…As it is expected, and also demonstrated by many other studies [63,64], LREE are generally enriched in monazite, allanite and carbonate minerals, whereas xenotime concentrates HREE regardless the conditions of crystallization. The highest average LREE concentrations at around 60 wt % occur in monazite, bastnäsite and synchysite, but the range of these values is highly variable.…”
Section: Compositions Of Ree Minerals With Different Origins In Finlandmentioning
confidence: 49%
“…Previous studies concluded that enrichments of REE is due to a combination of magmatic and hydrothermal processes [60,[63][64][65]. The 1.64-1.63 Ga Kymi Granite Complex can be divided into three varieties of rapakivi granite: (1) granite with ovoid alkali feldspar phenocrysts larger than 3 cm in diameter, mantled by sodic plagioclase.…”
Section: Rapakivi Granitementioning
confidence: 99%
See 1 more Smart Citation
“…This formation pattern of roquesite is similar to the mechanism of removal of invisible gold from arsenopyrite's crystalline lattice, which provoked the formation of independent aggregates upon a rise in temperature [44]. Experimental data [45] and the study of In-bearing base-metal mineralization in Kumi greisens from Vyborg rapakivi batholiths in southern Finland [46] suggest that In could have penetrated isomorphically into galena. Upon further alteration of galena, In may have been released from it, binding in its own mineralroquesite.…”
Section: Formation Of Roquesitementioning
confidence: 75%